PALB2 chromatin recruitment restores homologous recombination in BRCA1-deficient cells depleted of 53BP1 - Belotserkovskaya, Rimma (Nat Commun, 2020)
Loss of functional BRCA1 protein leads to defects in DNA double-strand break (DSB) repair by homologous recombination (HR) and renders cells hypersensitive to poly (ADP-ribose) polymerase (PARP) inhibitors used to treat BRCA1/2-deficient cancers. However, upon chronic treatment of BRCA1-mutant cells with PARP inhibitors, resistant clones can arise via several mechanisms, including loss of 53BP1 or its downstream co-factors. Defects in the 53BP1 axis partially restore the ability of a BRCA1-deficient cell to form RAD51 filaments at resected DSBs in a PALB2- and BRCA2-dependent manner, and thereby repair DSBs by HR. Here we show that depleting 53BP1 in BRCA1-null cells restores PALB2 accrual at resected DSBs. Moreover, we demonstrate that PALB2 DSB recruitment in BRCA1/53BP1-deficient cells is mediated by an interaction between PALB2’s chromatin associated motif (ChAM) and the nucleosome acidic patch region, which in 53BP1-expressing cells is bound by 53BP1’s ubiquitin-directed recruitment (UDR) domain.